CompTIA A+ 220-801 : (2012 objectives) - Long, Mark (InfiniteSkills, 2014)
"In this CompTIA A+ 220-801 training course, expert author Mark Long will teach you everything you need to know to prepare for a career in IT and successfully complete the A+ 220-801 exam. You will start by learning about PC hardware, including how to configure BIOS, motherboard basics, and the various expansion slot types. You will then learn about memory and storage, connectors, cables, and pins. This video tutorial will teach you about networking, wireless networking, and network types. You will learn about laptops, including laptop expansions and displays. Mark will teach you the basics of printers, the laser printing process, and how to manage and install a printer. Finally, you will learn the soft side of computing, the magic of communication, and how to deal with difficult customers. Once you have completed this computer based training course, you will have developed the knowledge and skills necessary to pass the A+ 220-801 exam."--Resource description page.